Simple Additive Weighting for Decision Support Selection of Expedition Services - Janti, Suhar; Adriansyah, Mohammad; Taufik, Ghofar (Sinkron : Jurnal dan Penelitian Teknik Informatika, 2020)
Freight forwarding services are increasingly developing and each delivery service provider competes to provide the best service, resulting in competition in terms of price and delivery time, in order to attract the attention of users of shipping services. The number of service providers with various types of packages offered by freight forwarding services, making users difficult in determining the right service provider. One way to overcome this problem is by the existence of a method that can provide recommendations as consideration for making appropriate decisions. This study aims to create a decision support system for the selection of goods delivery services by applying the Simple Additive Weighting method that can solve problems by comparing between shipping services. The results of this study are in the form of conclusion calculations that can be taken into consideration for decision making in choosing the most widely chosen freight forwarding services for students and getting the best results in decision making. The results of calculations using the Simple Additive Weighting method, the highest value based on time criteria is JNE YES with a value of 0.73, based on price criteria is a vehicle with a value of 0.68, based on the weight criteria is JNE YES with a value of 0.75, while based on the volume criteria the highest value is a vehicle with a value of 0.70 .